|
(P) qua C,⊥AH có PT : 1.(x−3)+1.(y−2)−2(z−3)=0⇔x+y−2z+1=0 B=(P)∩BM, tọa độ B thỏa mãn {x+y−2z+1=0x=1+t,y=4−2t,z=3+t ⇒t+1+4−2t−6−2t+1=0 ⇒t=0⇒B(1,4,3) - (Q) qua C,⊥BM có PT : 1.(x−3)−2(y−2)+1.(z−3)=0 ⇔x−2y+z−2=0 - K=(Q)∩BM, tọa độ K thỏa mãn : {x−2y+z−2=0x=1+t,y=4−2t,z=3+t⇒t=1,K(2,2,4) - E đối xứng với C qua K, tọa độ E xác định bởi : xE=2xK−xC=1,yE=2yK−yC=2,zE=2zK−zC=5 ⇒E(1,2,5) - A=BE∩AH,PT của BE:{x=1y=4−tz=3+t Tọa
độ A thỏa mãn : {x=1,y=4−t,z=3+tx−21=y−31=z−3−2⇔{x=1y=2z=5⇒A(1,2,5) AB=BC=CA=2√2⇒ΔABC đều
|
|
Trả lời 09-07-12 08:10 AM
|
|